1990
DOI: 10.1128/mcb.10.4.1642
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping, amplification, and overexpression of the mouse mdr gene family in multidrug-resistant cells.

Abstract: The mouse mdr gene family consists of three distinct genes (mdrl, mdr2, and mdr3), for which we have isolated full-length cDNA clones. cDNA subfragments corresponding to discrete regions showing little sequence conservation among the three mdr genes were used as gene-specific DNA probes in hybridization experiments. Long-range mapping by pulse-field gel electrophoresis indicated that the three mdr genes are closely linked on a genomic DNA segment of approximately 625 kilobases. The gene order and direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 35 publications
0
52
0
1
Order By: Relevance
“…Examples of closely linked gene families whose members have divergences in function are seen in the cases of the color-vision genes and the betaglobins (Nathans et al 1986;Yokoyama et al 1993;Fritsch et al 1980;Hardies et al 1984). Similarly, there are examples of the occurrence of closely linked gene copies that are redundant in function, such as is seen in the observed amplification of ribosomal RNA genes in various organisms and in the cellular aquisition of resistance to chemotherapeutic agents (Nath and Bollon 1977;Raymond et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Examples of closely linked gene families whose members have divergences in function are seen in the cases of the color-vision genes and the betaglobins (Nathans et al 1986;Yokoyama et al 1993;Fritsch et al 1980;Hardies et al 1984). Similarly, there are examples of the occurrence of closely linked gene copies that are redundant in function, such as is seen in the observed amplification of ribosomal RNA genes in various organisms and in the cellular aquisition of resistance to chemotherapeutic agents (Nath and Bollon 1977;Raymond et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…P-gp transports a wide range of structurally different therapeutics including colchicine, tacrolimus, quinidine, chemotherapeutic drugs (such as etoposide, doxorubicin, and vinblastine), cardiac glycosides (such as digoxin), glucocorticoids (such as dexamethasone), and human immunodeficiency virus type 1 antiretroviral therapy drugs (Aller et al, 2009). Overexpression of Abcb1a and -1b can confer drug resistance by increasing efflux of these drugs from cells (Dhir et al, 1990;Raymond et al, 1990) and is a well-established cause of resistance to cancer chemotherapeutic drugs. Abcb1a is mainly expressed in the gastrointestinal tract, testis, and capillaries within the brain (Cui et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] However, no associated genetic defect has been identified. It has The mouse mdr2 gene (standard gene symbol Pgy-been suggested that one subtype of PFIC may be attrib-3) and its human homolog MDR3 (also called MDR2, utable to a defect in primary bile acid secretion, 29 and it standard gene symbol PGY3) are members of the multi-has been established that children affected by another drug gene family [1][2][3][4][5][6][7] that do not confer multidrug resis-subtype have a defect in primary bile acid synthesis. 30 tance [8][9][10][11] but encode P-glycoproteins, which act as phos-In both of these subtypes, cholestasis is associated with phatidylcholine flippases.…”
mentioning
confidence: 99%